2014
DOI: 10.3991/ijet.v9i3.3347
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of E-learning at the University of Jordan

Abstract: Abstract-E-learning occupies a high place in universities and academic institutes and it is given the priority by the departments in these educational institutions. What we are witnessing today of the development of information technology and communications, networks, and multimedia is pushing us in the direction of the adoption of E-learning in education. The purpose of this study is to examine students' perception of E-learning at the University of Jordan based on Technology Acceptance Model. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 22 publications
2
47
0
2
Order By: Relevance
“…They concluded that there is a general acceptance of E-learning in universities in spite of the barriers which hinder the process of E-learning. Another research also support the findings also in which agrees with Almarabeh (2014) who stated that Jordanian students are very much qualified to utilize e-learning system then they are aware of E-learning benefits.…”
Section: Q1: What Are the Barriers Of Online Learning At Jerash Univesupporting
confidence: 84%
See 1 more Smart Citation
“…They concluded that there is a general acceptance of E-learning in universities in spite of the barriers which hinder the process of E-learning. Another research also support the findings also in which agrees with Almarabeh (2014) who stated that Jordanian students are very much qualified to utilize e-learning system then they are aware of E-learning benefits.…”
Section: Q1: What Are the Barriers Of Online Learning At Jerash Univesupporting
confidence: 84%
“…Previous research findings into the online barriers at local level have been inconsistent and contradictory (Almarabeh, 2014). He has conducted a study at the University of Jordan about the students' perceptions of e-learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, very little empirical research has been conducted on instructor adoption e-learning from the perspectives of user intention (Al-Shboul, 2013;Almarabeh, 2014;Nisperos, 2014). Therefore, it is critical to identify the factors that influence instructors adoption e-learning systems to help policymakers in higher education facilitate their use.…”
Section: Introductionmentioning
confidence: 99%
“…The e-learning method is not new to higher education and has increasingly been seen as a necessary development (Alavi & Gallupe, 2003). The more recent fast advancement of information and communication technology networks, as well as multimedia is pushing instructors in the direction of adopting e-learning methods (Almarabeh 2014;Tsai, Tsai, & Lin 2015;Gündüz, Alemdağ, Yaşar & Erdem 2016). While the traditional form of education still dominates, technology is argued to be effective in facilitating learning and assessment (Lai, Luo, Zhang, Huang, & Rozelle 2015, Sinkovics, Haghirian, & Yu 2009.…”
Section: Problem-based Learning and Assessmentmentioning
confidence: 99%
“…For example, an empirical study conducted by Almarabeh (2014) found that students in higher education institutions are not only highly qualified and accepting users of e-learning systems but with the desire to utilize them in even more advanced manners. In support of this finding, Sinkovics, Haghirian, & Yu (2009) and Lai, Luo, Zhang, Huang, & Rozelle (2015) find empirical evidence which suggests that e-learning environment (i.e.…”
Section: Problem-based Learning and Assessmentmentioning
confidence: 99%